Measurement of D-meson production at mid-rapidity in pp collisions at √s=7 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Ohlson, Alice; et al. (The European physical journal. C, Particles and fields, 2017)
The production cross sections for prompt charmed mesons D0D0D^0, D+D+D^+, D∗+D∗+\mathrm{D^{*+}} and D+sDs+D_s^+ were measured at mid-rapidity in proton-proton collisions at a centre-of-mass energy s√=7 TeVs=7 TeV\sqrt{s}=7~TeV with the ALICE detector at the Large Hadron Collider (LHC). D mesons were reconstructed from their decays D0→K−π+D0→K−π+D^0 → K^-π ^+, D+→K−π+π+D+→K−π+π+D^+→ K^-π ^+π ^+, D∗+→D0π+D∗+→D0π+D^{*+} → D^0 π ^+, D+s→ϕπ+→K−K+π+Ds+→ϕπ+→K−K+π+\mathrm{D_s^{+}→ φ π ^+→ K^-K^+π ^+}, and their charge conjugates.With respect to previous measurements in the same rapidity region, the coverage in transverse momentum (pTpTp_T) is extended and the uncertainties are reduced by a factor of about two. The accuracy on the estimated total cc¯¯cc¯c{\overline{c}} production cross section is likewise improved. The measured pTpTp_T-differential cross sections are compared with the results of three perturbative QCD calculations.
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, L. Leardini, J. Mercado Pérez, H. Oeschler, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, S. Schuchmann, J. Stachel, D.F. Weiser, J. Wilkinson, B. Windelband, A. Zimmermann [und weitere]
Gesehen am 28.09.2018